Typologies of Sufi Ulama in Tegal of Central Java during the Twentieth Century - Saepudin (Teosofia: Indonesian Journal of Islamic Mysticism, 2025)
Studies of Sufism in Java often focus on Sufi ulama in coastal areas, although Tegal is less exposed compared to other cities. This study examines the typologies of Sufi ulama in Tegal during the 20th century, including their biographical trajectories and scholarly relationships. Employing a historical qualitative approach supported by elements of social network analysis, the study identifies key figures who shaped the development of Sufism in the region and maps the patterns through which religious knowledge was transmitted across generations. The findings demonstrate that Sufism in Tegal is categorized into three main types: practical Sufism (ama>li>), ethical Sufism (akhla>qi>), and neo-Sufism. Sufi ulama in Tegal integrated shari'a-oriented learning with practical Sufism, thereby forming a localized style of Sunni-Neo-Sufism that was able to respond to the social and religious dynamics of the period. Contribution: This study contributes to the field of Javanese Sufism by expanding its scope to a relatively under-recognized region, namely Tegal, and by mapping the typology and scholarly chain of Sufis in the 20th century. These findings enhance our understanding of local variations in Javanese Sufism by illustrating the emergence of Sunni-Neo-Sufi patterns that adapt to local social and religious dynamics.